2019
DOI: 10.1007/s40820-019-0301-1
|View full text |Cite
|
Sign up to set email alerts
|

A New Free-Standing Aqueous Zinc-Ion Capacitor Based on MnO2–CNTs Cathode and MXene Anode

Abstract: HIGHLIGHTS • A new zinc-ion capacitor (ZIC) was realized by assembling the free-standing manganese dioxide-carbon nanotubes (MnO 2-CNTs) battery-type cathode and MXene (Ti 3 C 2 T x) capacitor-type anode in an aqueous electrolyte. • The large specific capacitance of the MXene anode avoids the mismatch in capacitance between the cathode and anode of the ZIC. • The superior performance of the proposed ZIC makes it a promising candidate for the next-generation energy storage devices. ABSTRACT Restricted by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(95 citation statements)
references
References 52 publications
2
93
0
Order By: Relevance
“…The 2D materials and their tailored products, such as black phosphorene and 0D graphene quantum dot (QD), have been employed as dopants to modify the SnO 2 ETLs in PSCs on the electrical conductivity, energy-level properties, and reducing the surface defects and surface electron traps [24,25]. As a new group of 2D materials, the MXene is constructed of M N+1 X N T X structure, where the M represents an early transition metal such as Ti, and the X representing C and/or N element, and the T X meaning the terminal functional groups [26]. With its excellent metallic electrical conductivity, hydrophilic surface, and pseudocapacitance properties, the MXene has been explored as electrode materials for solar cells [27][28][29], zinc-ion capacitors [26,30], supercapacitors [31], or sensors [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D materials and their tailored products, such as black phosphorene and 0D graphene quantum dot (QD), have been employed as dopants to modify the SnO 2 ETLs in PSCs on the electrical conductivity, energy-level properties, and reducing the surface defects and surface electron traps [24,25]. As a new group of 2D materials, the MXene is constructed of M N+1 X N T X structure, where the M represents an early transition metal such as Ti, and the X representing C and/or N element, and the T X meaning the terminal functional groups [26]. With its excellent metallic electrical conductivity, hydrophilic surface, and pseudocapacitance properties, the MXene has been explored as electrode materials for solar cells [27][28][29], zinc-ion capacitors [26,30], supercapacitors [31], or sensors [32].…”
Section: Introductionmentioning
confidence: 99%
“…As a new group of 2D materials, the MXene is constructed of M N+1 X N T X structure, where the M represents an early transition metal such as Ti, and the X representing C and/or N element, and the T X meaning the terminal functional groups [26]. With its excellent metallic electrical conductivity, hydrophilic surface, and pseudocapacitance properties, the MXene has been explored as electrode materials for solar cells [27][28][29], zinc-ion capacitors [26,30], supercapacitors [31], or sensors [32]. In PSC application, it has also been reported that the PCE can be enhanced on the basis of the improved functional layers with MXene dopant.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of carbon nanotubes (CNTs) by Iijima [1] led to extensive research for the utilization of these unique structures with extraordinary properties in the field of electrical storage devices [2,3], digital electronics devices [4,5], structure health monitoring (SHM) sensors [6,7] and concrete reinforcement applications [8,9], etc. Both theoretically and experimentally, it is proved that CNTs inherit excellent physical properties having an electrical conductivity of 3 × 10 6 S/m [10,11], the thermal conductivity of 2000-3500 W/m•K [12,13], the mechanical strength of 100 GPa [14], the Young's modulus of 1 TPa [15,16] and the piezoresistive gauge factor (GF) of 2900 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The GCD curves maintain the shape of the isosceles triangle, further indicating the excellent electrochemical performance of the MWCNTs‐RGO hybrid fibers. [ 41 ] The specific capacitance calculated by CV results of the MWCNTs‐RGO hybrid fibers are shown in Figure 3f. When the scan rates increased from 1 to 100 mV s −1 , the specific capacitance decreased from 134.1 to 38.0 F cm −3 .…”
Section: Resultsmentioning
confidence: 99%